Emerging Processes Within Peer-Support Hearing Voices Groups: A Qualitative Study in the Dutch Context - Schaefer, Barbara; Boumans, Jenny; van Os, Jim; van Weeghel, Jaap (Frontiers in Psychiatry, 2021)
Purpose / Aims: This study aimed to gain insight into whether and how Dutch Hearing Voices Groups (HVGs) contribute to the recovery process of people who hear voices. We focused specifically on the value of HVGs and the extent to which similar processes that take place in different groups add to this value. Method: The study used a qualitative design with in-depth interviews to explore the experiences of 30 members within seven HVGs in the Netherlands. Interviews were recorded, transcribed, and analyzed using interpretative analysis inspired by the Grounded Theory method. Findings: The individual-level analysis revealed four different group processes that appear to determine the value that HVGs have for their participants: (i) peer-to-peer validation, (ii) exchanging information and sharing self-accumulated knowledge, (iii) connection and social support, and (iv) engaging in mutual self-reflection. We found that specific characteristics of HVGs facilitate these group processes and lead to specific personal outcomes. Combining the interview data from people who joined the same HVG reveals that, although all four described group processes occur in all groups, each group’s emphasis differs. Three related factors are described: (i) the composition of the group, (ii) the style of the facilitators, and (iii) the interaction between group processes and individual processes. Implications: Unique processes, for which there is little to no place within regular mental health care (MHC), occur within HVGs. MHC professionals should be more aware of the opportunities HVG can offer voice-hearers. Essential matters regarding the implementation of HVGs are discussed.